Gujarati Translation and Psychometric Evaluation of the Craig Hospital Inventory of Environmental Factors–Short Form (CHIEF-SF) in Individuals with Spinal Cord Injury - Dr. Pallavi S. Variyani; Dr. Sandip Parekh; Dr. Bhavna Gadhavi (The Bioscan, 2025)
Background: Environmental conditions strongly influence social participation and community reintegration following spinal cord injury (SCI). The Craig Hospital Inventory of Environmental Factors–Short Form (CHIEF-SF) is a well-recognised tool to assessing environmental barriers; however, a Gujarati version has not been available. Objective: To translate, culturally adapt, and evaluate the psychometric properties of the CHIEF-SF for use with Gujarati-speaking individuals with SCI. Methods: The adaptation followed Beaton et al.’s standardized protocol. Two independent forward translations were prepared, synthesized, and then backtranslated. An expert committee reviewed all versions to confirm semantic, idiomatic, and conceptual accuracy. Pre-testing was conducted with 30 participants to ensure clarity and cultural fit. The finalized version was administered to a larger SCI sample for psychometric testing. Validity and reliability were assessed through content validity index (CVI), Cronbach’s alpha, intraclass correlation coefficient (ICC), standard error of measurement (SEM), minimal detectable change (MDC), and construct validity. Results: Content validity was excellent (S-CVI/Ave = 0.91). Internal consistency was high (Cronbach’s α = 0.87). Test–retest reliability was excellent (ICC = 0.92, 95% CI: 0.88–0.95). SEM and MDC95 values indicated acceptable precision. Construct validity was supported through significant negative correlations with participation measures (r = –0.62, p < 0.01). Conclusion: The Gujarati CHIEF-SF is a valid and reliable measure of environmental barriers in individuals with SCI and can support both clinical practice and policy development in Gujarat. KEYWORDS: Spinal cord injury, Environmental barriers, Psychometric testing, Cross-cultural adaptation, CHIEF-SF, Gujarati